User experiences of a mobile hospital clowning application: User-based evaluation with hospitalized children - Eira Erola; Johanna Viitanen; Kaisa Savolainen; Pekka Lahdenne (Finnish Journal of eHealth and eWelfare)
When developing digital health (eHealth) services targeted for pediatric patients, it is important to consider the needs and experiences of children as the end-users of the applications. However, hospitalized pediatric patients constitute a unique and vulnerable user group, and involving them in user-based evaluation studies presents specific challenges. Our aim was to study hospitalized pediatric patients’ user experience (UX) of a recently launched mobile hospital clowning application and to increase understanding of challenges related to studies with this special user group. Thus, we designed and conducted a user-based evaluation study with pediatric patients. The study data was gathered using remote interviews (n=3 participants) and an online questionnaire (n=6 respondents) in spring 2023. Based on the initial evaluation findings, the participants had positive UX with the application and found it easy to use. However, technical difficulties and improvement requests, particularly regarding the child-clown messaging and communication features, were also identified. Based on the reported study, our key learnings and recommendations for conducting user-based evaluations with hospitalized pediatric patients include: careful planning of ethical approval and a research permit for a non-medical study, employing multiple approaches for recruiting participants, adjusting research methods to suit for children, pilot testing the methods, and involving parents to help and assist the child participants. Despite challenges in study set-up, our evaluation resulted in usability and UX findings as well as areas for development for the hospital clowning application. This indicates that valuable insights on UX can emerge even from a small number of pediatric patients. Future work should focus on establishing sound practices for involving hospitalized pediatric patients in user-based evaluations of digital services and enhancing collaboration between researchers and children’s hospitals.